SENSITIVITY OF THREE THYROTROPIN RECEPTOR ANTIBODY ASSAYS IN THYROID-ASSOCIATED ORBITOPATHY: Sensitivity of TSH-R-Ab assays in TAO - Sarić Matutinović, Marija; Diana, Tania; Nedeljković Beleslin, Biljana; Ćirić, Jasmina; Žarković, Miloš; Perović Blagojević, Iva; Kahaly, George J.; Ignjatović, Svetlana (Journal of Medical Biochemistry, 2021)
Background: Thyrotropin receptor autoantibodies (TSH-R-Ab) are indispensable biomarkers in the laboratory assessment of thyroid-associated orbitopathy (TAO). Clinical sensitivity of three different assays for TSH-R-Ab determination was evaluated in patients with TAO.Methods: 87 consecutive TAO patients were enrolled and their serum samples analyzed in parallel with three assays. An ECLIA competitive binding and a chemiluminescent bridge immunoassay were used to measure total and binding TSH-R-Ab concentration, while their functional activity was determined using a stimulatory TSH-R-Ab (TSAb) cell-based bioassay.Results: Compared to the two binding assays (ECLIA p
Keywords: thyroid-associated orbitopathy, thyrotropin receptor antibodies, bioassay, bridge binding assay, ECLIA binding assay